2009
DOI: 10.1152/ajpheart.01288.2008
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-4 promotes induction of cardiomyocytes from human embryonic stem cells in serum-based embryoid body development

Abstract: Cardiomyocytes derived from human embryonic stem (ES) cells are a potential source for cell-based therapy for heart diseases. We studied the effect of bone morphogenetic protein (BMP)-4 in the presence of fetal bovine serum (FBS) on cardiac induction from human H1 ES cells during embryoid body (EB) development. Suspension culture for 4 days with 20% FBS produced the best results for the differentiation of early mesoderm and cardiomyocytes. The addition of Noggin reduced the incidence of beating EBs from 23.6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 45 publications
7
55
0
Order By: Relevance
“…Brachyury is also expressed at the cardiac precursor stage [33]. Previous work showed that BMP4 at 25 ng/ml concentration in combination with FBS at the appropriate time significantly promotes cardiomyocyte induction from human ES cells [34], consistent with the data generated in our study. We also analyzed the expression of Flk1 in all groups and observed that the levels of Flk1 in bFGF-induced cells were significantly increased at day 7 of differentiation and then sharply decreased thereafter.…”
Section: Discussionsupporting
confidence: 92%
“…Brachyury is also expressed at the cardiac precursor stage [33]. Previous work showed that BMP4 at 25 ng/ml concentration in combination with FBS at the appropriate time significantly promotes cardiomyocyte induction from human ES cells [34], consistent with the data generated in our study. We also analyzed the expression of Flk1 in all groups and observed that the levels of Flk1 in bFGF-induced cells were significantly increased at day 7 of differentiation and then sharply decreased thereafter.…”
Section: Discussionsupporting
confidence: 92%
“…Laflamme et al (2007) demonstrate that Bmp4 treatment increased in vitro cardiomyogenesis using human embryonic stem cells and Paige et al (2010) has elegantly shown a balanced interplay between activin A/Bmp4 and Wnt/-catenin is needed to efficiently induce mesodermal lineage formation and subsequent cardiomyocyte development in human embryonic stem cells. Similar findings are also observed using mouse embryonic stem cells (Taha et al, 2006(Taha et al, , 2007Taha & Valojerdi, 2008;Takei et al, 2009;Verma & Lenka, 2010). In addition to the role of Bmp signaling, several studies have reported the pivotal role of Fgf signaling controlling mouse embryonic stem cell-derived cardiomyogenesis (Dell´Era et al, 2003;Ronca et al 2009).…”
Section: Understanding Transcriptional Control Of In Vitro Cardiogenesissupporting
confidence: 72%
“…Wnt and PDGF signaling are regulated by the cilium in a series of other cell types involved in growth control, migration and differentiation (reviewed by Christensen et al, 2008;Gerdes and Katsanis, 2008). BMP promotes the induction of cardiomyocytes from the mouse stem cell line P19.SI (Angello et al, 2007) and human embryonic stem cells (Takei et al, 2009). Based on their findings on Pkd2 -/-mouse embryos, Slough and colleagues (Slough et al, 2008) also hypothesized that primary cilia in the heart and/or vasculature can function as mechanosensors to Immunofluorescence microscopy analysis of acetylated tubulin (tb) on primary cilia in the heart of E11.5 WT and Ift88-null mice (tb, red; DAPI, blue).…”
Section: Primary Cilia Are Important For Cardiogenesis In Vivomentioning
confidence: 99%